ANALISIS IMPLEMENTASI STRATEGI PEMASARAN DALAM MENINGKATKAN INVESTOR SAHAM OLEH PT PHINTRACO SEKURITAS DI KALIMANTAN TENGAH - Perdana Pardamean Silalahi, Randy; Riassy Christa, Usup; Tri Harinie, Luluk (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
An investor who wants to invest in stocks must have a stock account facilitated by a securities company. Many investors invest in stocks through PT Phintraco Sekuritas compared to other securities companies in Central Kalimantan. Therefore, this study aims to reveal the implementation of marketing strategies in increasing the number of stock investors carried out by PT Phintraco Sekuritas. The method used in this study is qualitative with SWOT data analysis. The SWOT analysis technique is used to assess the company's current situation, including strengths, weaknesses, opportunities, and threats, with reference to the 4P strategy aspects (Product, Place, Price, Promotion). Research results show that the number of stock investors in PT Phintraco Sekuritas in Central Kalimantan increased by an average of 74.62% per year, with the highest growth rate in 2017 at 255%.. Based on the research results, the implementation of marketing to increase the number of stock investors by PT Phintraco Securities in Central Kalimantan has its greatest strengths in the product and promotion strategy factors, and has opportunities in the Place and Promotion factors.